The association of oxidative stress markers with conventional risk factors in the metabolic syndrome - Korkmaz, Gulcan G.; Altinoglu, Esma; Civelek, Sabiha; Sozer, Volkan; Erdenen, Fusun; Tabak, Omur; Uzun, Hafize (W B SAUNDERS CO-ELSEVIER INC, 2013)
Background and Aims. The metabolic syndrome (MetS) is a common and complex disorder that consists of various abnormalities, including dyslipidemia, obesity, hypertension and hyperglycemia. We investigated the relationships between the levels of advanced protein oxidation products (AOPPs), the total antioxidant capacity (TAC) and the pro-oxidant-antioxidant balance (PAB) in MetS patients. Methods. A total of 55 patients (37 women, 18 men) with MetS and 20 healthy controls (14 women, 6 men) with a body mass index (BMI) less than 25 kg/m(2) were enrolled in the study. Colorimetric methods were used to determine the levels of AOPPs, the TAC, and the PAB. Results. AOPP, TAC, and PAB values were significantly higher in patients with MetS than in control subjects (p<0.001, p = 0.050, and p<0.001, respectively). A positive correlation was observed between the AOPP levels and the glucose, triglyceride, insulin and HOMA-IR levels. PAB values also exhibited significant positive correlations with diastolic blood pressure and fibrinogen levels. Logistic regression analysis revealed that higher serum PAB values were positively and independently associated with the MetS (odds ratio: 1.110; 95% confidence interval: 1.006-1.224; P<0.37). Conclusions. Increased AOPP levels and higher PAB values are likely to be a result of oxidative stress, a condition in which an imbalance occurs between the production and inactivation of reactive oxygen species. In addition, it appears that serum PAB values may accurately reflect the levels of oxidative stress in MetS patients. Crown Copyright (C) 2013 Published by Elsevier Inc. All rights reserved.
Keywords: Metabolic syndrome; Advanced protein oxidation products; Total antioxidant capacity; Pro-oxidant-antioxidant balance; PROOXIDANT-ANTIOXIDANT BALANCE; URIC-ACID; OBESITY; PARAOXONASE; PARAMETERS; CAPACITY; COMPONENTS; ADULTS; Endocrinology & Metabolism